ANALISIS PENILAIAN TINGKAT KESEHATAN PT BPR ALTO MAKMUR PERIODE 2017-2021 DENGAN METODE CAMEL - Lely Ajeng Susilawati; Ida Savitri Kusmargiani; Septia Yudha Kusuma (Fakultas Ekonomi Prodi Akuntansi, 2022)
This reseacrh aims to assess and analyze the level of health bank using the CAMEL method at PT BPR Alto Makmur 2017-2021. Based on the Decree of the Board of Directors of Bank Indonesia No. 30/12/KEP/DIR dated April 30, 1997, there are five factors in assessing the soundness of a bank using the CAMEL method, namely the capital factor using the CAR (Capital Adequacy Ratio), the productive assets quality factor using the KAP (Earning Assets Quality) and PPAP (Allowance for Earning Assets Losses), management factors use general management and risk management calculations, profitability factors use ROA (Return On Assets) and BOPO (Operational Expenses to Operating Income) ratio, and liquidity factors use Cash Ratio and LDR (Loan to Deposit Ratio). The results of research conducted at PT BPR Alto makmur stated that the health level of PT BPR Alto Makmur in 2017-2021 was in the HEALTHY category because the final CAMEL score was more than 81, namely in 2017 amounting to 89,10, 2018 amounting to 89, 2019 amounting to 88,80, 2020 amounting to 89,30, and 2021 amounting to 89,10.